Effect of chitosan-poly(acrylic acid) complexes and two nutrient solutions on the growth and yield of two habanero pepper cultivars - Palacios Torres, Rogelio Enrique; Santos-Chávez, Amadeo; Ortega-Ortiz, Hortensia; Ramírez Seañez, Ana Rosa; Yam Tzec, José Antonio; Amador Mendoza, Adolfo; Juárez-Maldonado, Antonio; Reyes Osornio, Maribel; Hernández Hernández, Hipólito (MDPI AG, 2022)
Chitosan (CS) is a natural polymer used in agriculture as a biostimulant that has been evaluated in different plant models. In this study, we evaluated the effect of the foliar application of chitosan–poly(acrylic acid) complexes (CS–PAA) and two nutrient solutions (A and B) on the parameters of growth and yield of two habanero pepper cultivars (Chichen Itza and Jaguar) in a greenhouse. Over the course of the experiment, eight foliar applications were carried out at 15-day intervals. Our results showed that foliar applications of CS–PAA complexes have a biostimulant effect on the habanero pepper crop by increasing the total dry biomass of the plant and the number of fruits of the two cultivars. Regarding nutrient solutions, the nutrient solution A increased the yield of the Chichen Itza cultivar; this effect was because it had a better balance of potassium and calcium compared to the nutrient solution B. These results provide advances on the use of CS–PAA complexes as a biostimulant and the management of nutrient solutions in the crop of habanero peppers.
Keywords: Bioestimulante; Complejos; Solución nutritiva; Invernaderos; Capsicum chinense